The philosophers and the Bible: the debate on sacred scripture on early modern thought - Del Prete, Antonella; Schino, Anna Lisa; Totaro, Pina (Brill's studies in intellectual history, 2021)
Intro -- Contents -- Figures -- Notes on Contributors -- Introduction -- Part 1 Enquiring on Moses -- Chapter 1 Images of Moses in the Renaissance -- Chapter 2 More on Spinoza and the Authorship of the Pentateuch -- Part 2 Prophet's Witnessing -- Chapter 3 Tommaso Campanella on the Bible Ontology, Epistemology and Political Philosophy -- Chapter 4 Prophecy and the Prophetic Kingdom of God in the Hobbesian Analysis of the Holy Scriptures -- Chapter 5 Hermeneutics and Conflict Spinoza and the Downfall of Exegetical Interpretation -- Part 3 Rational Theology and Natural Religion -- Chapter 6 The Bible in the Philosophy of Anne Conway and Henry More -- Chapter 7 "Between Doubt and Knowledge" John Biddle and the English Unitarians in the Time of Locke -- Chapter 8 Immorality and Intolerance in the Bible? Natural Ethicality and the Interpretation of Scripture in the Writings of Pierre Bayle -- Part 4 The Moral Message of the Bible -- Chapter 9 Peace and Truth in Polemic: Pascal's Pensées L974/S771 -- Chapter 10 An Association without Power? Gift, Recognition, and Democracy in the Hobbesian Conception of Early Christian Communities -- Chapter 11 "The Law Inscribed in the Mind" On the Meaning of a Biblical Image in Spinoza's Theological-Political Treatise -- Part 5 The Accommodation Doctrine -- Chapter 12 Firmamentum La querelle théologico-philologique du ciel étoilé, de Copernic à Kepler -- Chapter 13 L'exégèse du dernier Mersenne et le cartésianisme -- Chapter 14 "Accommoder la Théologie à ma façon de philosopher" Descartes and Dutch Cartesians Interpreting the Bible -- Chapter 15 Wolff, Spinoza, and the Interpretation of Scripture -- Chapter 16 Natural Philosophy and Scripture in Isaac Newton's Principia mathematica -- Index Nominum.